Structure-functional characterization of cytochrome P4502E1 (CYP2E1) - Danko, I.M.; Chaschin, N.A. (Біополімери і клітина, 2007)
This review summarizes data on expression level and localization, structure and functional properties of cytochrome P4502E1 (CYP2E1). Induction of CYP2E1 synthesis and activity by compounds with various chemical structures and under certain pathophysiological states is considered. Special emphasis is placed on CYP2E1 expression inhibitors. The latest data on CYP2E1 expression regulation and degradation mechanisms are analyze. В огляді узагальнено результати дослідження рівня експреси, і локалізації, структури і функціональних властивостей цитохрому Р4502Е1 (CYP2E1). Розглянуто механізми індукції синтезу і активності CYP2E1 різними за хімічною структурою сполуками, а також за деяких патофізіологічних станів організму. Значну увагу приділено інгібіторам експресії CYP-2Е1. Проаналізовано останні дані відносно механізмів регуляції експресії CYP2E1 та його деградації. В обзоре обобщены результаты исследования уровня экспрессии и локализации, структуры и функциональных свойств цитохрома Р4502Е1 (CYP2E1). Рассмотрены механизмы индукции синтеза и активности CYP2E1 различными по химической структуре соединениями, а также при некоторых пато-физиологических состояниях организма. Значительное внимание уделено ингибиторам экспрессии CYP2EL Проанализированы последние данные относительно механизмов регуляции экспрессии CYP2EJ и его деградации.